2016
DOI: 10.1007/jhep05(2016)114
|View full text |Cite
|
Sign up to set email alerts
|

A 750 GeV diphoton signal from a very light pseudoscalar in the NMSSM

Abstract: The excess of events in the diphoton final state near 750 GeV observed by ATLAS and CMS can be explained within the NMSSM near the R-symmetry limit. Both scalars beyond the Standard Model Higgs boson have masses near 750 GeV, mix strongly, and share sizeable production cross sections in association with b-quarks as well as branching fractions into a pair of very light pseudoscalars. Pseudoscalars with a mass of ∼ 210 MeV decay into collimated diphotons, whereas pseudoscalars with a mass of ∼ 500-550 MeV can de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 128 publications
(210 reference statements)
0
21
0
Order By: Relevance
“…This mixing effect has already been noted in the context of heavy quarkonia [16,27] and its impact on A 1 -decays at the bb-threshold was highlighted in [56]. In the very low-mass range, [57] suggested that the hadronic decays of A 1 may resemble those of the meson that is closest in mass, while [58] estimated the mixing with the mesons in the formalism of Partially-Conserved Axial Currents (PCAC). As a consequence of this confused situation for the pseudoscalar decays, the phenomenology of this particle at low-mass remains largely speculative and the interplay of constraints cannot be consistently applied.…”
Section: Jhep03(2017)052mentioning
confidence: 74%
“…This mixing effect has already been noted in the context of heavy quarkonia [16,27] and its impact on A 1 -decays at the bb-threshold was highlighted in [56]. In the very low-mass range, [57] suggested that the hadronic decays of A 1 may resemble those of the meson that is closest in mass, while [58] estimated the mixing with the mesons in the formalism of Partially-Conserved Axial Currents (PCAC). As a consequence of this confused situation for the pseudoscalar decays, the phenomenology of this particle at low-mass remains largely speculative and the interplay of constraints cannot be consistently applied.…”
Section: Jhep03(2017)052mentioning
confidence: 74%
“…2.1.2. In the NMSSM one can explain this excess by assuming the presence of additional final states via four-body decays like → (φ a )(φ a ) → 4γ γ [173,183]. This explanation requires the mass of φ a to be tiny and very close to the pion mass.…”
Section: Sarahmentioning
confidence: 99%
“…If the invisible decay mode of the resonance, which is less constrained, is responsible for a large width of the resonance, there is an interesting possibility that the resonance plays a role of mediator between the SM and dark matter [30,[37][38][39][40][41][42][43][44][45][46][47][48][49]. On the other hand, there is a plausible option to explain the diphoton excesses with collimated photons, the so called photon-jets, which come from a cascade decay of the resonance into a pair of light mediators, each of them decaying into a pair of photons [50][51][52][53][54][55][56][57]. In this case, the width of the resonance can be increased by a renormalizable coupling between the resonance and the light mediator.…”
Section: Jhep07(2016)030mentioning
confidence: 99%